Introduction of Ecobricks at Mi Al-Muhajirin as an Effort to Control Plastic Waste - Andra Putra Hendri; Angelina Theresia; Dhini Akika Putri; Ioyz Zahrani; Melinda; Natasya Putri Edella; Oasis Sifra Elisabet; Rahma Fadila Amalia; Salsi Gustialen Putri (Indonesian Journal of Advanced Social Works, 2023)
Plastic waste is a problem that Indonesia has not been able to overcome. Even though plastic waste has a negative impact on the environment. Plastic waste management, especially in schools, is still not optimal. Ecobricks are a waste management technique by placing waste in plastic bottles and compacting them. Ecobrick educational activities were carried out at MI Al-Muhajirin, Kijang Rejo Village, Tapung District, Kampar Regency by The Student Study Service from University of Riau. Activities are carried out using socialization and direct practice methods. This service activity succeeded in making students enthusiastic about making ecobricks and motivated to protect the environment from the dangers of plastic waste.